2006
DOI: 10.1007/s00425-006-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

Red light causes a reduction in IAA levels at the apical tip by inhibiting de novo biosynthesis from tryptophan in maize coleoptiles

Abstract: When maize coleoptiles were unilaterally exposed to red light (7.9 micromol m(-2)s(-1) for 5 min), 3 h after treatment IAA levels in coleoptiles decreased in all regions, from top to basal, with levels about 60% of dark controls. Localized irradiation in the 5 mm top zone was sufficient to cause the same extent of IAA reduction in the tips to that in the tips of whole irradiated shoots. When coleoptiles were treated with N-1-naphthylphthalamic acid (NPA), an accumulation of IAA in the tip and a decrease of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…Recently, understanding of the plant physio- logical or developmental outcomes caused by light quality has increased (Folta and Maruhnich, 2007;Galen et al, 2007;Nishimura et al, 2006). Interesting experimental results have demonstrated that significant differences in the traits of horticultural relevance of diploid strawberry plants were observed under a blue/ red light mixture conditions (Folta and Childers, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, understanding of the plant physio- logical or developmental outcomes caused by light quality has increased (Folta and Maruhnich, 2007;Galen et al, 2007;Nishimura et al, 2006). Interesting experimental results have demonstrated that significant differences in the traits of horticultural relevance of diploid strawberry plants were observed under a blue/ red light mixture conditions (Folta and Childers, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…S9) by gas chromatographyselected ion monitoring-mass spectroscopy (GC-SIM-MS) as described (45,46). To investigate polar IAA transport in IR64 and NIL-SPIKE coleoptiles, we applied 3 μM IAA to the top of coleoptile sections (1.5-3.0 mm) for 30 min, then incubated the coleoptiles on an agar block for 10 min and measured the transported IAA by GC-SIM-MS as above.…”
Section: Transformation Of Spikementioning
confidence: 99%
“…IAA purification and measurement were performed as described previously by Nishimura et al (2006) with the following minor modifications. To extract free IAA from tissues, 6-d-old Arabidopsis roots (10-35 mg fresh weight) were placed in 2.0-mL tubes with 180 mL of cold 80% methanol containing 0.1 mg mL 21 2,6-di-tert-butyl-4-methylphenol and 2.0 to 4.0 ng of [ 13 C 6 ]IAA (Cambridge Isotope Laboratories) as well as a small amount of glass beads.…”
Section: Extraction and Determination Of Free Iaamentioning
confidence: 99%